Study and design of a Magnetic Levitator System - Meneses Claudio, Brian (2019)
Magnetic levitation is one of the mechanisms that is at the forefront of technology. It is used in its most basic form in educational teaching, where the principles of physics converge that have as their principle electromagnetism and the fields created by existing poles that repel according to a quantity of initial current, giving instructive ideas of how the theoretical formulas work, giving life to a practical visual system. The current use on a large scale are the Maglev trains of Japan or superconductivity, being the realization of the quantum effects visualized at the moment of cooling the sample. The electronic circuit tends to be stable because, when using a high-power current, a Triac is needed to compensate the electrical flow provided by the operational amplifier and, therefore, stabilize with the photodiode when activated with the Led diode. Our purpose is to create a circuit that identifies the values of the electronic components that allow reaching equilibrium, with input and output variables that indicate the position and height of the object to be levitated.